School conflict frameworks: A comparative approach on two secondary schools of Córdoba, Argentina - Guido García Bastán; IIPsi CONICET / UNC; Marina Edith Tomasini; IDH CONICET / UNC (Escuela de Psicología, Pontificia Universidad Católica de Valparaíso, 2019)
In Argentina, the measuring of violence and school conflict has contributed to relativize the importance of socio-economic variables in the production of these phenomena. However, qualitative research on these issues continues to study schools from low-income sectors as a priority. By action or omission, there is a kind of "eclipse" of the day-to-day life of the upper- class that could contribute to building conflict as a trait of vulnerable schools and, by extension, of their students. In this work, from a qualitative approach, we comparatively address some aspects of daily conflict in two schools in the city of Córdoba Capital. Our analysis supports the hypothesis that conflict in different social sectors may not differ completely in its types of demonstrations, although it does differ in the situational connotations that the incidents acquire, according to the frameworks from which they are interpreted. These frameworks reveal a moralization of incidents, which seems to operate differently in the production of moral subjects, an aspect that should be addressed in the design of coexistence policies.